2012
DOI: 10.1590/s1806-83242012000400016
|View full text |Cite
|
Sign up to set email alerts
|

Influence of core-finishing intervals on tensile strength of cast posts-and-cores luted with zinc phosphate cement

Abstract: The core finishing of cast posts-and-cores after luting is routine in dental practice. However, the effects of the vibrations produced by the rotary cutting instruments over the luting cements are not welldocumented. This study evaluated the influence of the time intervals that elapsed between the cementation and the core-finishing procedures on the tensile strength of cast posts-and-cores luted with zinc phosphate cement. Forty-eight bovine incisor roots were selected, endodontically treated, and divided into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…Small variations must be considered in some factors such as room temperature, cement time and handling speed, time spent to be taken to the canal and core, pressure from the operator hand at the preparation time, among others, may have interfered in the results, since the other conditions had been fully satisfied Results similar to this study were found in the studies of Lund & Wilcox 14 , Rocha et al 15 , Domingos et al 16 , Iglesias 17 and Oliveira et al 18 , concluding that the preparation time after cementation does not interfere with the retention of cores cemented with zinc phosphate cement.…”
Section: Resultssupporting
confidence: 76%
“…Small variations must be considered in some factors such as room temperature, cement time and handling speed, time spent to be taken to the canal and core, pressure from the operator hand at the preparation time, among others, may have interfered in the results, since the other conditions had been fully satisfied Results similar to this study were found in the studies of Lund & Wilcox 14 , Rocha et al 15 , Domingos et al 16 , Iglesias 17 and Oliveira et al 18 , concluding that the preparation time after cementation does not interfere with the retention of cores cemented with zinc phosphate cement.…”
Section: Resultssupporting
confidence: 76%
“…9,10 For decades, zinc phosphate cement has been the gold standard for cementing cast post and cores, although resin luting agents have recently been studied as alternatives. 11 Many researchers use glass ionomer cement for cementing post. But, glass ionomer cement has several limitations and has been criticized by several authors, 12,13 whereas resin cement is more expensive and its bonding to the metallic post is questionable unless a primer is used for bonding.…”
Section: Discussionmentioning
confidence: 99%